Experimental investigation of CFRP strengthened I-shaped cold formed steel beams - Chakravarthy N.; Naganathan S.; Aun J.T.H.; Kalavagunta S.; Mustapha K.N.; Veena T.R. (Penerbit UTM Press, 2023)
Cold formed steel differ from hot rolled steel by its lesser thickness and weight. The cold formed steel applicable in roof purlin, pipe racks and wall panels etc. Due its lesser wall thickness the cold formed steel member subjected to buckling. The enhancement of load carrying capacity of the cold formed steel member can be achieved by external strengthening of CFRP. In this study cold formed channel members connected back to back to form I shaped cross section using screws. These built up beam members were 300mm, 400mm and 500mm in length with 100mm screw spacing and edge distance of 50mm were chosen for testing. CFRP fabric cut according to length, width of built up beams and wrapped outer surface of beam using epoxy resin. Experiments were carried out in two sets firstly plain built up beams and secondly CFRP wrapped beams. The test results shows that increased load carrying capacity and reduction in deflection due to CFRP strengthening. Experimental results were compared with AISI standards which are in good agreement. Experimental results shows that CFRP strengthening is economic and reliable. 2017 Penerbit UTM Press. All rights reserved.